Study of Relativity Theory of Einstein: The Story of Ashabul Kahf and Isra’ Mi’raj - Fitria Mercyta Celina; Nadi Suprapto (Indonesia Approach Education, 2020)
Al Qur’an is the greatest miracle that used as a guide for Muslims in the world. In it contains several verses that are relevant to physics. The study aims to examine Einstein’s Theory of Relativity in the story of Ashabul Kahf and Isra’ Mi’raj of Prophet Muhammad SAW. A qualitative approach is used with the library research method by analyzing related books and journals. The result show that the relativity time of angles and humans can be explained by Einstein’s Theory of Relativity. Einstein’s Theory of Relativity has nothing to do with the Ashabul Kahf event. However, for the events of Isra’ Mi’raj of prophet Muhammad SAW, Einstein’s Theory of Relativity is not sufficient to prove it.